Aberrant allele-switch imprinting of a novel IGF1R intragenic antisense non-coding RNA in breast cancers. Issue 2 (January 2015) - Kang, Lihua; Sun, Jingnan; Wen, Xue; Cui, Jiuwei; Wang, Guanjun; Hoffman, Andrew R.; Hu, Ji-Fan; Li, Wei
Abstract The insulin-like growth factor type I receptor (IGF1R) is frequently dysregulated in breast cancers, yet the molecular mechanisms are unknown. A novel intragenic long non-coding RNA (lncRNA) IRAIN within the IGF1R locus has been recently identified in haematopoietic malignancies using RNA-guided chromatin conformation capture (R3C). In breast cancer tissues, we found that IRAIN lncRNA was transcribed from an intronic promoter in an antisense direction as compared to the IGF1R coding mRNA. Unlike the IGF1R coding RNA, this non-coding RNA was imprinted, with monoallelic expression from the paternal allele. In breast cancer tissues that were informative for single nucleotide polymorphism (SNP) rs8034564, there was an imbalanced expression of the two parental alleles, where the 'G' genotype was favorably imprinted over the 'A' genotype. In breast cancer patients, IRAIN was aberrantly imprinted in both tumours and peripheral blood leucocytes, exhibiting a pattern of allele-switch: the allele expressed in normal tissues was inactivated and the normally imprinted allele was expressed. Epigenetic analysis revealed that there was extensive DNA demethylation of CpG islands in the gene promoter. These data identify IRAIN lncRNA as a novel imprinted gene that is aberrantly regulated in breast cancer.